Left behind the public education crisis in the United States - Jalbert, Paul L. (Routledge, 2018)
"This book addresses the harmful influences that the cultural, social, economic, political and ideological dimensions, in current 'American' society, have upon the delivery of elementary, secondary and university education. It examines the effects of poverty, funding at the local, state and federal levels and racial and ethnic discrimination. Arguing against the continuation of standardized testing--an ill-conceived methodology to measure the performance of children--the author advocates more one-on-one teaching and evaluation. He charges that students' rights to education are not respected and, in elementary and high school, receive little in the way of instruction that translates into life skills and proposes what some of those skills should be. A critique of the extreme ethnocentric approach to education in the United States, Left Behind advocates strong instruction in the Humanities and foreign languages and the establishment of education abroad as a permanent program in high school and university"--Provided by publisher.